Table of Contents

Last modified on August 20th, 2024

To convert a mixed number to its corresponding improper fraction, we follow the following steps:

**Step 1: Multiplying the Denominator with the Whole Number**

Here,

Denominator = 5

Whole number = 1

Now, by multiplying 5 and 1, we get

5 × 1 = 5

**Step 2: Adding the Numerator to the Product**

Here,

Product = 5

Numerator = 2

Now, adding 2 to it, we get

5 + 2 = 7

**Step 3: Writing in Improper Fraction Form**

Mathematically, the improper fraction is written as

${\dfrac{\left( Denominator\times Whole \ Number\right) +Numerator}{Denominator}}$

Thus, the improper fraction is ${\dfrac{7}{5}}$

Let us convert ${3\dfrac{1}{2}}$ into improper fraction,

**Step 1: Multiplying the Denominator with the Whole Number**

Here,

Denominator = 2

Whole number = 3

Now, by multiplying 2 and 3, we get

2 × 3 = 6

**Step 2: Adding the Numerator to the Product**

Here,

Product = 6

Numerator = 1

Now, adding 1 to it, we get

6 + 1 = 7

**Step 3: Writing in Improper Fraction Form**

${3\dfrac{1}{2}= ${\dfrac{7}{2}}$

Thus, the mixed number ${3\dfrac{1}{2}}$ as an improper fraction is ${\dfrac{7}{2}}$

**Convert ${2\dfrac{2}{3}}$ to improper fraction.**

Solution:

As we know, ${\dfrac{\left( Denominator\times Whole \ Number\right) +Numerator}{Denominator}}$

Here,

The denominator = 3

The numerator = 2

The whole number = 2

Now, ${2\dfrac{2}{3}=\dfrac{\left( 2\times 3\right) +2}{3}}$ = ${\dfrac{8}{3}}$

Thus, the improper fraction is ${\dfrac{8}{3}}$

**Write the mixed number ${7\dfrac{4}{13}}$ as improper fraction.**

Solution:

As we know, ${\dfrac{\left( Denominator\times Whole \ Number\right) +Numerator}{Denominator}}$

Here,

The denominator = 13

The numerator = 4

The whole number = 7

Now, ${7\dfrac{4}{13}=\dfrac{\left( 7\times 13\right) +4}{13}}$ = ${\dfrac{95}{13}}$

Thus, the improper fraction is ${\dfrac{95}{13}}$

**Turn the mixed number ${6\dfrac{1}{6}}$ into improper fraction.**

Solution:

As we know, ${\dfrac{\left( Denominator\times Whole \ Number\right) +Numerator}{Denominator}}$

Here,

The denominator = 6

The numerator = 1

The whole number = 6

Now, ${6\dfrac{1}{6}=\dfrac{\left( 6\times 6\right) +1}{6}}$ = ${\dfrac{37}{6}}$

Thus, the improper fraction is ${\dfrac{37}{6}}$

**Change ${4\dfrac{1}{2}}$ into improper fraction.**

Solution:

As we know, ${\dfrac{\left( Denominator\times Whole \ Number\right) +Numerator}{Denominator}}$

Here,

The denominator = 2

The numerator = 4

The whole number = 1

Now, ${4\dfrac{1}{2}=\dfrac{\left( 4\times 2\right) +1}{2}}$ = ${\dfrac{9}{2}}$

Thus, the improper fraction is ${\dfrac{9}{2}}$

Last modified on August 20th, 2024